Tendencias y perspectivas del marketing en las pymes - Suárez Pérez, Juan Carlos (2021)
The research understands and analyzes the current situation of marketing strategies in Small and medium-sized enterprises (SMEs), since it has been shown that they are designed empirically, that is, without a technical support that guarantees the success of planning for their development and sustainability. Likewise, the study delves into the reality of these organizations, and the marketing trends and perspectives that fit their needs to make them more competitive and position themselves in the market. In this sense, the objective is to analyze the trends and perspectives of marketing in SMEs in the city of Ambato, for this, a qualitative methodology was applied, which allowed contextualizing and investigating natural, holistic and flexible information. The results are part of the determination of the strategic planning of SMEs in the city under study; in order to improve its operation, consolidate its brand and digitize businesses in the future, no matter how small they may be, since this contributes to their own positioning, through the optimization of resources, the improvement of technology and the possibility of applying more efficient strategies that make them grow and expand.